The Implementation Of Strategic Management During The Covid-19 Pandemic - St. Syamsudduha; Ridwan Idris; Mardhiah; Akbar Fajrin (Proceedings of Annual Conference on Islamic Educational Management, 2021)
The research’s aim is to describe the Implementation of Strategic Management during the Covid-19 Pandemic in SMAN 1 Wajo. Good Strategic Management will support the success of the school in achieving the schools’ vision that has been designed. In the process of compiling, there are several stages including Formulating, Implementing, and Evaluating. This study is a qualitative research with a phenomenological approach that uses interviews, observations, and documentation in data collection techniques. Data processing is done through data analysis of the interactive analysis model from Miles & Hubberman, namely: reducing data, presenting data, and concluding or continuously verifying, in the form of cycles. The results of the study found that the Implementation of Strategic Management during the Covid-19 Pandemic in SMA Negeri 1 Wajo went well and adapted to the changing conditions of the learning process as the result of online learning policies in achieving the goals set in the midst of the Covid 19 pandemic. The strategic formulation process begins with composing vision and mission, SWOT analysis and making short, medium and long term strategic plans. School strategic management is applied to the National Education Standards, then evaluated every two weeks by the principal which is presented at school meeting held at the end of month. The challenges in the implementation process are the lack of student motivation in participating in the Study From Home process during the pandemic as well as teacher discipline in teaching, parents economic level and the Covid-19 clusters in Wajo Regency.